Dampak penyediaan sumur bor terhadap kualitas kesehatan dan ekonomi pedesaan: Kasus Indonesia - Leksono, Agung Bowo (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2024)
Water is essential for daily economic activities. This study examines the impact of borehole water access on rural health and economy, focusing on reducing diarrhea and boosting small industries. Using data from PODES 2014-2021 and a 2019 borehole program, control villages with similar characteristics were selected. The sample includes 4,550 villages. DiD analysis show the policy does not significantly affect diarrhea prevalence or small industries. Boreholes may not meet all residents' needs, and factors like location and industrial suitability might reduce interest in using water for businesses.